Culinary Heritage and Sustainable Development: Exploring the Role of Food Tourism in Promoting Local Economies and Cultural Identity in Nigeria - Eba, Maxwell-Borjor Achuk; Apeh, Apeh Columba; Egbe, Boypa Oyama (dialektika kontemporer, 2025)
Food tourism in Nigeria represents a dynamic intersection between cultural heritage and economic opportunity, offering a unique lens through which to explore the nation’s diverse culinary traditions and their potential for sustainable development. This study investigates how food tourism can serve as a catalyst for economic empowerment, cultural preservation, and regional identity in Nigeria. Drawing on qualitative field research, stakeholder interviews, and analysis of regional food festivals, the paper examines the evolving role of local cuisines in shaping domestic and international tourist experiences. It argues that traditional Nigerian dishes—such as pounded yam and egusi, suya, tuwo shinkafa, and banga soup—are not only vehicles for cultural expression but also instruments for community development when integrated into broader tourism frameworks. The paper also evaluates government policies, private sector investments, and grassroots initiatives that support culinary tourism. Special attention is paid to the challenges facing the sector, including infrastructure deficits, lack of standardized food safety practices, and limited international visibility. Ultimately, the study advocates for a strategic alignment between food tourism and national development goals, emphasizing the need for targeted investments, cultural branding, and stakeholder collaboration to unlock Nigeria’s full potential as a food tourism destination..